Congenital Cholesteatoma in Adult: Is it Still Possible? (Bangladesh Journal of Otorhinolaryngology, 2021)
Congenital cholesteatoma is a mass of squamous epithelium located medial to an intact tympanic membrane without previous history of tympanic membrane perforation, otorrhoea or otological surgery. We described a 24 year old gentleman with a left postauricular discharging fistula for 3 years with recent history of gradual hearing loss, tinnitus and recurrent episodes of positional vertigo. Clinical examination noted left postauricular fistula opening and otoscopy showed a whitish mass medial to a bulging intact tympanic membrane. High-resolution computed tomography of temporal bone was suggestive of cholesteatoma. Left modified radical mastoidectomy was done and he recovered with resolution of symptoms.Bangladesh J Otorhinolaryngol; April 2021; 27(1): 96-99